2019
DOI: 10.1038/s41598-019-55875-4
|View full text |Cite
|
Sign up to set email alerts
|

A de novo EGR2 variant, c.1232A > G p.Asp411Gly, causes severe early-onset Charcot-Marie-Tooth Neuropathy Type 3 (Dejerine-Sottas Neuropathy)

Abstract: EGR2 (early growth response 2) is a crucial transcription factor for the myelination of the peripheral nervous system. Mutations in EGR2 are reported to cause a heterogenous spectrum of peripheral neuropathy with wide variation in both severity and age of onset, including demyelinating and axonal forms of Charcot-Marie Tooth (CMT) neuropathy, Dejerine-Sottas neuropathy (DSN/CMT3), and congenital hypomyelinating neuropathy (CHN/CMT4E). Here we report a sporadic de novo EGR2 variant, c.1232A > G (NM_000399.5), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The most common phenotypes for infantile-onset patients were DSS in our findings. Genetically, most cases are caused by a dominant or de novo mutation in the PMP22, MPZ or EGR2 genes (Gargaun et al, 2016;Grosz et al, 2019;Yoshimura et al, 2019). In addition to PMP22 mutations, variants in rare genes, e.g., EGR2, PRX, and FGD4 were found more frequently due to the introduction of NGS and WES, which was consistent with previous studies (Yoshimura et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…The most common phenotypes for infantile-onset patients were DSS in our findings. Genetically, most cases are caused by a dominant or de novo mutation in the PMP22, MPZ or EGR2 genes (Gargaun et al, 2016;Grosz et al, 2019;Yoshimura et al, 2019). In addition to PMP22 mutations, variants in rare genes, e.g., EGR2, PRX, and FGD4 were found more frequently due to the introduction of NGS and WES, which was consistent with previous studies (Yoshimura et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, the IEGs investigated this study are also related to disorders of the central nervous system. For example, associations have been found between EGR1 and Alzheimer's disease 44 , EGR2 and Charcot-Marie-Tooth disease 45 47 , EGR3 and schizophrenia 48 50 , and c-Jun and Krox24 (EGR1) and Alzheimer's disease 51 . In nerve cells, the expression of IEGs encoding transcription factors, such as c-Fos and EGR1, is induced by an increase in intracellular Ca 2+ as a result of synaptic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the Early-Growth Response 2 (EGR2) gene (OMIM #129010) provoke demyelinating Charcot-Marie-Tooth (CMT) disease type 1D (CMT1D, OMIM #607678), congenital hypomyelinating neuropathy type 1 (CHN1, OMIM #605253), Déjerine-Sottas syndrome (DSS, OMIM #145900), and axonal CMT (CMT2). [1][2][3][4][5][6][7][8][9][10][11] EGR2 gene encodes for a zinc finger (ZNF) transcription factor crucial for peripheral nervous system (PNS) myelination and it is hypothesized EGR2 gene mutations disrupt PNS myelination program, thus provoking a wide spectrum of demyelinating neuropathies ranging from early-onset severe variants such as CHN1 and DSS, to late-onset moderate variants such as CMT1D. [1][2][3][4][5][6][7][8][9][10][11] More recently, it has been shown that EGR2 gene mutations also provoke axonal CMT2-like neuropathies, indicating a role for EGR2 in axonal maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] EGR2 gene encodes for a zinc finger (ZNF) transcription factor crucial for peripheral nervous system (PNS) myelination and it is hypothesized EGR2 gene mutations disrupt PNS myelination program, thus provoking a wide spectrum of demyelinating neuropathies ranging from early-onset severe variants such as CHN1 and DSS, to late-onset moderate variants such as CMT1D. [1][2][3][4][5][6][7][8][9][10][11] More recently, it has been shown that EGR2 gene mutations also provoke axonal CMT2-like neuropathies, indicating a role for EGR2 in axonal maintenance. 12,13 EGR2 gene mutations causing demyelinating neuropathy were identified in 1998 and more than 25 different mutations have been described since then.…”
Section: Introductionmentioning
confidence: 99%